Recuperating the bad outcome: reimagining optimal futures beyond Auditory Verbal Therapy and Applied Behavioral Analysis. (2nd January 2023) - Friedner, Michele; Block, Pamela
ABSTRACT: This article analyzes convergences in the ways that both deafness and autism are framed as crises that require immediate (and often expensive) professional intervention. Parents receive messages that failure to therapeutically intervene will prevent their children from living normative lives. We demonstrate how therapy techniques such as Auditory Verbal Therapy and Applied Behavioral Analysis have proliferated to address these crises. We explore the development of professional organizations and training programs devoted to AVT and ABA and we consider how AVT and ABA professionals define "optimal outcomes" that are supposedly achieved when diagnosis is removed or declassified. In contrast to professional views, we argue for alternative perceptions of these therapeutic processes and their ostensible outcomes based on accounts by d/Deaf and Autistic adults. In addition, we argue that the (neutral) language of outcomes obscures the active work required and backgrounds the different kinds of labor and ideologies at play. While AVT and ABA experts argue that it is increasingly possible to achieve optimal outcomes, we question the sensory and relational costs of these outcomes and the way that they prevent other ways of being, sensing, and communicating from taking place.